NILAI WAJAR SAHAM PADA KUALITAS LABA - Anggraini, Francisca Reni Retno (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
This research aims to investigate the effect of unrealized gains and losses of marketable securities from 19 firms in banking, insurance, credit agencies, and securities industries to earnings quality. The research periods are taken from 2001-2005 becaused of the effective date of PSAK 30 and 50 that related with banking accounting and valuation of securities is December 31th, 2001. There is no volatiles difference between unrealized gains and losses of marketable securities and net income before extraordinary items and unrealized gains and losses of marketable securities persisten from year to year. It is interesting, because theoretically fair value accounting yields higher volatility in earnings. It indicate that manager manages risk by smooths unrealized gains and losses of marketable securities because the high volatility of them cause volatility of earnings increase and finally cost of capital increase so investors do not interest to invest their capital. Finally, this research finds that there is negative correlation of unrealized gains and losses of marketable securities and accrual quality. It indicates that fair value accounting can not increase objectivity of financial statements.